Determinants of related and unrelated corporate diversification and impact on performance of Malaysian listed companies - Chan, Ling Foon (2018)
Corporate diversification is a strategy enabling corporations to expand their core business into other businesses. In Malaysia, corporate diversification continued to be a fundamental organisational structure, where 2/3 of Malaysian firms are diversified. However, when compared to developed countries, such as the US and UK, firms are moving towards non-diversification. The research objectives are to analyse the impact of corporate diversification, related and unrelated diversification on firm's financial performance and to measure ownership concentration, free cash flow and growth opportunities on firm’s financial performance. The study is based on the population framework consisting of all the public listed companies (PLC) listed on the Bursa Malaysia from 2007 to 2012. A dynamic panel model System Generalized Method of Moments (GMM) was used to analyse the diversification and firm performance theory. The research provides answers to close the literature gaps, by using Entropy and relatedness, which reflected more on the actual degree of diversification better than those conventionally used dummy variable methods that were unable to explain the degree of the diversification. The empirical finding which showed diversified is better than non-diversified firms which take into consideration the quadratic relationship between diversification and firm performance (ROA) using entropy Index and relatedness. The researcher further reported that not enough evidence has showed that related or unrelated diversification brings negative effect to firm financial performance or quadratic effect in corporate diversification. The researcher did not have enough evidence to support that ownership structure (family ownership (FO) or government ownership (GO) and free cash flow (FCF) have any effect on firm performance, and there is also not enough evidence to support the moderation effect of ownership structure and free cash flow (FCF) toward corporate diversification and firm financial performance. However, in growth opportunity, the researcher did find out that growth opportunity does bring negative effect to firm performance. The reason may be due to some agency issues related to empire building and tunnelling effect. Besides that, growth opportunity also has positive moderate effect on corporate diversification and firm performance significant at 1% level. The more the firm has the growth opportunity, the more the firm will do diversification. In the end, this causes the negative effect in corporate performance. As per control variables, size and crisis are positively correlated with the firm financial performance as significant at 10 % and 5% level. The future research should begin to explore on market concentration of the firm in the industries by using Herfindahl-Hirschman index (HHI) to measure corporate diversification and firm performance in the market concentration basic.